Rancang Bangun Aplikasi Recruitment Karyawan Baru Menggunakan Metode Naive Bayes Classifier Di PT. Batavia Prosperindo Finance Tbk Kota Bengkulu - Feisal, Royki; Suranti, Dewi; Fredricka, Jhoanne (INCODING: Journal of Informatics and Computer Science Engineering, 2022)
PT. Batavia Prosperindo Finane Tbk Bengkulu City is one of the companies engaged in the financing of four-wheeled vehicles. Since its inception on December 12, 1994, as a Multifinance Company, BPF has obtained a business license for a Financing Institution from the Ministry of Finance of the Republic of Indonesia which includes Financial Lease, Factoring, Credit Card and Consumer Finance. The company has not used a special application in determining the selection of new employee recruitment, and is still using it manually like one-on-one for the selection of new employees, so it is possible that the selection of employees is often long. One method that can solve this problem is by using the naive bayes classifier method, because the naive bayes classifier method is a method for solving multiple decision-making criteria, so the final calculation result has a probability for data analysis of new employee recruitment as the final output. Based on the results of observations using 50 applicant data, of which 30 data is accepted and 20 data is not accepted. With this method, it helps the company to find out which probability is the greatest to be able to help in overcoming the existing problems